Patients’ evaluations of patient safety in English general practices: a cross-sectional study - Ricci Cabello, I; Marsden, K; Avery, A; Bell, B; Kadam, U; Reeves, D; Slight, S; Perryman, K; Barnett, J; Litchfield, I; Thomas, S; Campbell, S; et al. (Royal College of General Practitioners, 2017)
Background The frequency and nature of safety problems and harm in general practices has previously relied on information supplied by health professionals, and scarce attention has been paid to experiences of patients. Aim To examine patient-reported experiences and outcomes of patient safety in Primary Care in England. Design and Setting Cross-sectional study in 45 general practices Method A postal version of the Patient Reported Experiences and Outcomes of Safety in Primary Care (PREOS-PC) questionnaire was sent to a random sample of 6,736 patients. Main outcome measures included “practice activation” (what does the practice do to create a safe environment); “patient activation” (how pro-active are patients in ensuring safe healthcare delivery); “experiences of safety events” (safety errors); “outcomes of safety” (harm); and “overall perception of safety” (how safe do patients rate their practice). Results 1,244 patients (18.4%) returned completed questionnaires. Scores were high for “practice activation” (mean (standard error) = 80.4 out of 100 (2.0)) and low for “patient activation” (26.3 out of 100 (2.6)). A substantial proportion of patients (45%) reported having experienced at least one safety problem in the previous 12 months, mostly related to appointments (33%), diagnosis (17%), patient-provider communication (15%), and coordination between providers (14%). 221 patients (23%) reported some degree of harm in the previous 12 months. The overall assessment of the level of safety of their practices was generally high (86.0 out of 100 (16.8)). Conclusion Priority areas for patient safety improvement in general practices in England include appointments, diagnosis, communication, coordination and patient activation.